Utilizing State Sharia Securities (SBSN) as an Alternative Financing Mechanism for Madrasah Infrastructure Development - Munir Munir; Rimi Gusliana Mais; Juniarti Juniarti; Lina Noersanti (Transpublika Publisher, 2026)
Indonesia continues to face significant challenges in providing adequate educational infrastructure, particularly for madrasahs, due to budget limitations and increasing student enrollment demands. In response, the government has utilized State Sharia Securities (Surat Berharga Syariah Negara/SBSN) as an alternative Islamic financing instrument to support public infrastructure development. This study analyzes the utilization of State Sharia Securities (Surat Berharga Syariah Negara/SBSN) as an alternative financing mechanism for madrasah infrastructure development at the Jakarta Regional Office of the Ministry of Religious Affairs. The research employs a qualitative approach using a case study method. Data were collected through interviews, observations, and document analysis involving stakeholders responsible for SBSN-funded projects. The findings reveal that SBSN has played a significant role in supporting the construction of new classroom buildings and improving the quality of madrasah educational infrastructure in Jakarta. Through the SBSN financing scheme, madrasahs have been able to increase classroom capacity, enhance educational facilities, and accommodate growing student enrollment demands. The implementation process involves coordination among the Ministry of Religious Affairs, the Ministry of Finance, and the National Development Planning Agency (Bappenas). However, several challenges remain, including land readiness, administrative procedures, maintenance costs, and technical infrastructure limitations. This study concludes that SBSN represents a strategic and sustainable alternative financing mechanism for public educational infrastructure development. Strengthening institutional coordination, improving project planning, and enhancing monitoring systems are necessary to optimize the effectiveness of SBSN implementation in supporting the development of madrasah infrastructure in Indonesia.